2007
DOI: 10.1017/s1751731107727489
|View full text |Cite
|
Sign up to set email alerts
|

Production of trans C18:1 and conjugated linoleic acid in continuous culture fermenters fed diets containing fish oil and sunflower oil with decreasing levels of forage

Abstract: Previously, feeding fish oil (FO) and sunflower seeds to dairy cows resulted in the greatest increases in the concentrations of vaccenic acid (VA, t11 C18:1) and conjugated linoleic acid (CLA) in milk fat. The objective of this study was to evaluate the effects of forage level in diets containing FO and sunflower oil (SFO) on the production of trans C18:1 and CLA by mixed ruminal microbes. A dual-flow continuous culture system consisting of three fermenters was used in a 3 £ 3 Latin-square design. Treatments c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Since FO in the diet causes an increase in trans-C18:1 and trans-C18:2 intermediates and a reduction in the flow of C18:0 leaving the rumen it has been postulated (Offer et al, 1999;Shingfield et al, 2003;Lee et al, 2005) that one or more long-chain n-3 fatty acids or biohydrogenation intermediates from FO specifically inhibit the growth and activity of Group B bacteria known to hydrogenate C18:1 to C18:0. In support of this, C22:6n-3 was shown to be associated with the accumulation of trans-C18:1 intermediates in vitro (AbuGhazaleh and Jenkins, 2004;AbuGhazaleh and Jacobson, 2007). In this experiment, the decrease in C18 PUFA flow at the duodenum and corresponding increase in C18 MUFA and PUFA biohydrogenation in response to incremental amounts of FO in the diet is in marked contrast to the observations that C20:5n-3 and C22:6n-3 decrease cis-9 C18:1 and C18:2n-6 biohydrogenation in vitro (AbuGhazaleh and Jenkins, 2004;AbuGhazaleh and Jacobson, 2007).…”
Section: Rumen Functionmentioning
confidence: 74%
See 1 more Smart Citation
“…Since FO in the diet causes an increase in trans-C18:1 and trans-C18:2 intermediates and a reduction in the flow of C18:0 leaving the rumen it has been postulated (Offer et al, 1999;Shingfield et al, 2003;Lee et al, 2005) that one or more long-chain n-3 fatty acids or biohydrogenation intermediates from FO specifically inhibit the growth and activity of Group B bacteria known to hydrogenate C18:1 to C18:0. In support of this, C22:6n-3 was shown to be associated with the accumulation of trans-C18:1 intermediates in vitro (AbuGhazaleh and Jenkins, 2004;AbuGhazaleh and Jacobson, 2007). In this experiment, the decrease in C18 PUFA flow at the duodenum and corresponding increase in C18 MUFA and PUFA biohydrogenation in response to incremental amounts of FO in the diet is in marked contrast to the observations that C20:5n-3 and C22:6n-3 decrease cis-9 C18:1 and C18:2n-6 biohydrogenation in vitro (AbuGhazaleh and Jenkins, 2004;AbuGhazaleh and Jacobson, 2007).…”
Section: Rumen Functionmentioning
confidence: 74%
“…In support of this, C22:6n-3 was shown to be associated with the accumulation of trans-C18:1 intermediates in vitro (AbuGhazaleh and Jenkins, 2004;AbuGhazaleh and Jacobson, 2007). In this experiment, the decrease in C18 PUFA flow at the duodenum and corresponding increase in C18 MUFA and PUFA biohydrogenation in response to incremental amounts of FO in the diet is in marked contrast to the observations that C20:5n-3 and C22:6n-3 decrease cis-9 C18:1 and C18:2n-6 biohydrogenation in vitro (AbuGhazaleh and Jenkins, 2004;AbuGhazaleh and Jacobson, 2007). This variation in response across the two studies may be related to an effect of FO inhibiting some bacteria and allowing others to proliferate which may also be involved in lipolysis and biohydrogenation and/or there are other active agents in FO other than these specific long-chain PUFA, such as fatty acid oxidation products which have been shown to have antimicrobial properties (Lee et al, 2007b).…”
Section: Rumen Functionmentioning
confidence: 74%
“…Treatment diets and effluent samples were methylated using the sodium methoxide (NaOCH 3 ) and HCl two-step procedures as outlined by Kramer et al (1997) and analyzed in duplicate for FA as described by Gas Liquid Chromatography (GLC) as described by AbuGhazaleh and Jacobson (2007). Apparent biohydrogenation was calculated from C18:1n9, C18:2n6 and C18:3n3 proportions in dietary and effluent C18 FA, assuming that the total C18 FA input equals the total C18 FA output (Lourenç o et al, 2008).…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…Different dietary strategies have been used to decrease the rate of ruminal BH such as feeding plant and marine oils (AbuGhazaleh and Jacobson, 2007;Gudla et al, 2012), or algae (AbuGhazaleh et al, 2009) and increasing forage to concentrate ratio (AbuGhazaleh and Jacobson, 2007). Several feed additives have been also proposed to increase the content of CLA in milk fat.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that DHA may restrain rumen bacterial growth, thereby decreasing the hydrogenation of unsaturated FA, resulting in an increased level of TVA and a decreased level of C 18:0 (Griinari and Bauman, 1999). Other researchers have reported that the accumulation of TVA caused by fi sh oil supplementation in the diet results from inhibition of a reductase in the rumen microorganisms that are responsible for the terminal hydrogenation of TVA to C 18:0 (Wasowska et al, 2006;AbuGhazaleh et al, 2007). Interestingly, we found that the TVA and cis-9, tran-11 CLA content was affected by sampling time.…”
Section: Discussionmentioning
confidence: 39%